Penyelesaian Tindak Pidana Cukai Antara Korp Polisi Air dan Udara Badan Pemeliharaan Keamanan Kepolisian Republik Indonesia Dengan Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tipe Madya Pabean B Jambi di Wilayah Perairan Kuala Tungkal Tanjung Jabung Barat - Suratni, Suratni; Sahabuddin, S; Suzanalisa, Suzanalisa (Universitas Batanghari Jambi, 2025)
Excise levy, which is one component of state revenue that has special characteristics and is different from other tax levies, one of the areas that has the potential for state revenue is the Kuala Tungkal Waters Region of West Tanjung Jabung, so synergy is carried out between the Air and Water Police Corps Institution of the Indonesian National Police Security Maintenance Agency and the Jambi Customs and Excise Supervision and Service Type Madya Customs B Office. So it is interested in conducting research that aims to understand and analyze the implementation, constraints and efforts in the synergy of the Air and Water Police Corps of the Indonesian National Police Security Maintenance Agency with the Jambi Customs and Excise Supervision and Service Office Type Madya Customs B in the Kuala Tungkal Waters of West Tanjung Jabung. The research method uses an empirical juridical approach. It is necessary to improve the performance of the synergy of the Office of Customs Supervision and Services of the Jambi Customs Madya Type B and the Korpolairud Barhakam Polri in resolving excise crimes in the Kuala Tungkal waters of West Tanjung Jabung. investigation, especially the rat lines of smuggling of excise goods. So that this research can provide advice on the ability, integrity of investigators of the Jambi Customs and Excise Supervision and Service Office of Customs Type B and the Korpolairud Barhakam Polri in solving excise crimes in the Kuala Tungkal waters of West Tanjung Jabung and public awareness in the Kuala Tungkal waters of West Tanjung Jabung in legal awareness of the importance of excise and law enforcement of excise crimes in the context of development in Indonesia